Measurement of electron-positron spectrum in high-energy cosmic rays in the PAMELA experiment. (July 2015) - Karelin, A V; Adriani, O; Barbarino, G C; Bazilevskaya, G A; Bellotti, R; Boezio, M; Bogomolov, E A; Bongi, M; Bonvicini, V; Bottai, S; Bruno, A; Cafagna, F; et al.
Abstract: At present the existing data on the cosmic ray electron energy spectra in the high energy range are fragmented, and the situation is exacerbated by their small number. In the satellite PAMELA experiment measurements at high energies are carried out by the calorimeter. The experimental data accumulated for more than 8 years of measurements, with the information of the calorimeter, the neutron detector and the scintillation counters made it possible to obtain the total spectrum of high-energy electrons and positrons in energy range 0.3-3 TeV.